1998
DOI: 10.1126/science.280.5365.912
|View full text |Cite
|
Sign up to set email alerts
|

Chaos, Persistence, and Evolution of Strain Structure in Antigenically Diverse Infectious Agents

Abstract: The effects of selection by host immune responses on transmission dynamics was analyzed in a broad class of antigenically diverse pathogens. Strong selection can cause pathogen populations to stably segregate into discrete strains with nonoverlapping antigenic repertoires. However, over a wide range of intermediate levels of selection, strain structure is unstable, varying in a manner that is either cyclical or chaotic. These results have implications for the interpretation of longitudinal epidemiological data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
339
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(363 citation statements)
references
References 12 publications
21
339
3
Order By: Relevance
“…The empirical evidence for the type of cross-immunity between serotypes therefore does not unequivocally support a particular model, e.g. Kamo & Sasaki (2002) versus Gupta et al (1998), but a combination of models. The particular choice of model, however, does not affect our general conclusion (results not shown).…”
Section: The Mathematical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The empirical evidence for the type of cross-immunity between serotypes therefore does not unequivocally support a particular model, e.g. Kamo & Sasaki (2002) versus Gupta et al (1998), but a combination of models. The particular choice of model, however, does not affect our general conclusion (results not shown).…”
Section: The Mathematical Modelmentioning
confidence: 99%
“…Alternative definitions and models for cross-immunity exist (e.g. Andreasen et al 1997;Gupta et al 1998;Gog & Swinton 2002); we use this representation because volunteer studies have shown that patients re-challenged with the heterologous serotype of cholera rarely become infected. When symptoms do occur, they are milder and V. cholerae excretion levels are reduced (Cash et al 1974), arguing for a concomitant reduction in transmissibility, which is not incorporated in the model framework we use here.…”
Section: The Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst the detailed structure and magnitude of the pattern of these timeseries di¡er, it is striking to note that all suggest signi¢-cant three-or four-year oscillations in dengue infection incidence. Clearly, before such a conclusion can be de¢ni-tively con¢rmed, analysis of other strati¢ed serological surveys will be required, but it is supported by data from hospitalization reports (Briseno-Garcia et al 1996) and clinical observation (Dove 1998 transmission dynamics of the virus (Ferguson et al 1999;Gupta et al 1998), where they are generated by immunemediated competition or cooperation between strains.…”
Section: Applicationmentioning
confidence: 99%
“…Organisms such as influenza and pneumococcus have well-established interactions [18] and vaccination for one may have additional benefits in preventing a proportion of another infection which is not estimable from this analysis. In addition the impact of vaccination for a subgroup of types, as proposed for the pneumococcus, may have unpredictable results [19].…”
Section: Discussionmentioning
confidence: 99%